Pendidikan dan Pelatihan Digital Marketing Melalui E-Commerce untuk Meningkatkan Performa Bisnis Masyarakat di Desa Ciwalat, Kec. Pabuaran, Kab. Sukabumi - Ubaidillah, Aldi; Nurhayanti, Melda Dwi; Nurdiyanto, Nurdiyanto; Setiawan, Wahyu Adjie; Melati, Dewi Sukma; Kasmad, Kasmad; Sudaryana, Yayan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This service is titled Digital Marketing Education and Training Through E-commerce to Improve Community Business Performance in Ciwalat Village, Pabuaran District, Sukabumi Regency. This service was held on Sunday, June 2, 2024 which was attended by 20 students and 6 Supervisors of Pamulang University. The general purpose of this community service activity is to provide training and knowledge about digital marketing through the Marketplace (Shopee) in an effort to improve Micro, Small and Medium Enterprises (MSMEs) and community welfare in Ciwalat Village, Pabuaran District, Sukabumi Regency. The methods used are survey methods and direct delivery of material as well as simulations and discussions on management, financial management, product marketing and the application of human resource management (HRM). This service activity succeeded in providing understanding to the community, especially MSMEs, regarding product marketing carried out through digital marketing through the marketplace (shopee) in an effort to develop businesses or businesses of the Ciwalat Village community.